2020
DOI: 10.1101/2020.12.18.423407
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-color fluorescence fluctuation spectroscopy in living cells via spectral detection

Abstract: Fluorescence fluctuation spectroscopy provides a powerful toolbox to quantify transport dynamics and interactions between biomolecules in living cells. For example, cross-correlation analysis of spectrally separated fluctuations allows the investigation of inter-molecular interactions. This analysis is conventionally limited to two fluorophore species that are excited with a single or two different laser lines and detected in two non-overlapping spectral channels. However, signaling pathways in biological syst… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 68 publications
0
10
0
Order By: Relevance
“…Ternary complex detection has been achieved with triple correlation analysis (TRICS), but that relies on higher order correlation functions which greatly increase the signal-to-noise requirements for the data and computational complexity (17,38). Additionally, visual inspection of covariance matrices allows for the straightforward observation of complex formation that has an intuitive connection to the emission spectra (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ternary complex detection has been achieved with triple correlation analysis (TRICS), but that relies on higher order correlation functions which greatly increase the signal-to-noise requirements for the data and computational complexity (17,38). Additionally, visual inspection of covariance matrices allows for the straightforward observation of complex formation that has an intuitive connection to the emission spectra (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…To this aim, we selected HEK293T cells as a cellular model because they are often used for reverse genetic virus production [40, 41, 79], were shown to be appropriate for IAV protein expression [17, 42, 43] and are better suited for quantitative fluorescence fluctuation analysis of proteins at the PM, compared to other cell lines [80]. Additionally, we produced and tested several fluorescent IAV protein constructs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our control experiments showed that the cellular distribution of M1 with an mEGFP fused to its C-terminus was similar to that of unlabeled M1 [44, 63], whereas an N-terminally fused mEGFP M1 variant seemed to have transport failures which are probably caused by steric hindrance between fluorophore and signal peptide [44]. On the other hand, the fluorescent constructs used to investigate the viral envelope proteins (HA, NA, and M2) were all localized at the PM, similar to the corresponding non-fluorescent proteins [65, 66], and yielded the expected oligomerization state [42, 43, 69, 70]. For example, our results are compatible with the presence of NA tetramers and mixtures of M2 dimers and tetramers (Figure 3C), in agreement with previous data [71, 83].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations